2018
DOI: 10.1590/2175-8239-jbn-3824
|View full text |Cite
|
Sign up to set email alerts
|

NOS3 Polymorphisms and Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is a multifactorial pathophysiologic irreversible process that often leads to a terminal state in which the patient requires renal replacement therapy. Most cases of CKD are due to chronic-degenerative diseases and endothelial dysfunction is one of the factors that contribute to its pathophysiology. One of the most important mechanisms for proper functioning of the endothelium is the regulation of the synthesis of nitric oxide. This compound is synthesized by the enzyme nitric oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…These results are consistent with previous studies that demonstrate that a lack of eNOS À/À -derived NO impaired mitochondrial beta-oxidation leads to accumulation of fat, 32 which has a critical influence on lipid metabolism. 30,31,62 Remarkably, many human chronic diseases, like insulin resistance, type 2 diabetes, and obesity are associated with a deficiency in the eNOS À/À expression and/or function, 23,63 highlighting the role of NO in the pathophysiology of NAFLD. The current study strongly supports a causal role of NO in maintaining a healthy liver and, in its absence, promoting NAFLD progression in the context of obesity and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies that demonstrate that a lack of eNOS À/À -derived NO impaired mitochondrial beta-oxidation leads to accumulation of fat, 32 which has a critical influence on lipid metabolism. 30,31,62 Remarkably, many human chronic diseases, like insulin resistance, type 2 diabetes, and obesity are associated with a deficiency in the eNOS À/À expression and/or function, 23,63 highlighting the role of NO in the pathophysiology of NAFLD. The current study strongly supports a causal role of NO in maintaining a healthy liver and, in its absence, promoting NAFLD progression in the context of obesity and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…At the kidney level NO performs several functions related to renal and glomerular hemodynamics; its most important effects at that level are to promote diuresis and natriuresis, as well as the regulation of renin secretion [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…NOS3 catalyses the production of nitric oxide (NO), which is closely related to endothelial cell function, and vascular endothelial dysfunction has been considered an important factor in the pathogenesis of DN ( Zeng et al, 2010 ). Other studies have shown that the polymorphism of the NOS3 gene is related to the rapid deterioration of renal function in CKD patients ( Medina et al, 2018 ); PTGS-2 is a key enzyme in the initiation of prostaglandin synthesis in vivo and is a major target of NSAIDs for treatment ( Vane, 1971 ; Flower, 1974 ). It mainly causes diabetic renal damage by mediating inflammation and affecting renal haemodynamics ( Morham et al, 1995 ; Martín-Sanz et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%